Analisis Keterampilan Mengajar Mahasiswa Pendidikan Guru Sekolah Dasar pada Mata Kuliah Micro Teaching - Dhea Divana Anggreni; Desryanti Manurung; Santa Grace Naibaho; Nurleli Hasibuan; Nurmayani Nurmayani; Maya Alemina Ketaren (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study examines the teaching skills of Elementary School Teacher Education students in micro teaching courses through literature study. The purpose of the research is to analyze the mastery of basic teaching skills and the factors that influence it. The method used is a literature study with a focus on theoretical aspects and references to scientific literature analyzed using the content analysis method. The research findings show that micro teaching plays an important role in equipping students with basic teaching skills such as opening and closing lessons, asking questions, providing reinforcement, explaining material, and managing the class. However, mastery of teaching skills has not been evenly distributed among students due to lack of practical experience, limited training time, and suboptimal guidance. Internal factors such as self-confidence and communication skills and external factors such as the quality of mentors and laboratory facilities also affect student performance. The implication is that innovation is needed in the implementation of micro teaching, increasing the duration of practice, using technology for reflection, and strengthening the role of supervisors as facilitators and evaluators to prepare competent and professional prospective elementary teachers.